Reviewing pictures in planning wind energy projects: How a reasoned visual discourse may be fostered through participatory process design - Horelt, Michel; Carius, Rainer; Ewen, Christoph (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Planning processes of windfarms are often characterised by image conflicts. Conflicting parties use visualisations of the planned project to picture the assumed impact on the landscape and to underscore their opposing positions to the project. For observers and decision-makers (e.g. municipal leaders, administrators) it is often difficult to distinguish realistic visualisations from manipulative ones. This paper presents ways in which observers may acquire a competence in “reading” and assessing visualised windfarms – similar to the critical competence in assessing the validity of media sources. The paper also presents criteria for the different states of the visualisation process – from the context of pro[1]duction, to image processing to modes of presentation. These criteria render pictures more transparent and thus may help observers base their interpretations on sounder reasoning. Drawing on social constructivist theories of landscape inter pretation and on extensive experience in conflict moderation, the paper demonstrates how a public planning dialogue, in which contradicting pictures claim validity, may be designed in order to clarify the value of each visualisation for the public.